1984
DOI: 10.1159/000176776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Guar-Enriched Pasta in the Treatment of Diabetes and Hyperlipidemia

Abstract: The effect of an alimentary pasta with a 20% (w/w) content of Guar gum was tested in normal volunteers, diabetic and hyperlipidemic patients in different out- and in-patient protocols. Acute experiments (A, B) were carried out in healthy volunteers and in diabetics, by evaluating plasma glucose, triglyceride and insulin changes after a single meal. Plasma glucose and triglyceride rises were almost completely prevented by the pasta in normal volunteers; plasma insulin levels were modified to a lesser extent. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…Alguns estudos in vivo relatam que a suplementação com fibras viscosas diminui a resposta glicêmica frente a uma ingestão elevada de hidratos de carbono 10,16,20,32,62 . A causa deste efeito, segundo os autores, pode estar na ação dos polissacarídeos viscosos sobre as propriedades físicas do conteúdo intestinal, porém este mecanismo fisiológico não está totalmente esclarecido, já que existem outros fatores que podem contribuir para este fenômeno, tais como: o atraso no esvaziamento gástrico, que segundo alguns autores seria o principal fator na modificação da movimentação intestinal; a redução na velocidade de difusão da glicose nas células da mucosa e, por último, o aumento da viscosidade do conteúdo intestinal e a diminuição do acesso da enzima alfa-amilase a seu substrato.…”
Section: Resultsunclassified
“…Alguns estudos in vivo relatam que a suplementação com fibras viscosas diminui a resposta glicêmica frente a uma ingestão elevada de hidratos de carbono 10,16,20,32,62 . A causa deste efeito, segundo os autores, pode estar na ação dos polissacarídeos viscosos sobre as propriedades físicas do conteúdo intestinal, porém este mecanismo fisiológico não está totalmente esclarecido, já que existem outros fatores que podem contribuir para este fenômeno, tais como: o atraso no esvaziamento gástrico, que segundo alguns autores seria o principal fator na modificação da movimentação intestinal; a redução na velocidade de difusão da glicose nas células da mucosa e, por último, o aumento da viscosidade do conteúdo intestinal e a diminuição do acesso da enzima alfa-amilase a seu substrato.…”
Section: Resultsunclassified
“…Although a dose-response trial has not been completed, guar gum doses in the range of 1.8-15 g have been found to improve the postprandial glycemic response to oral glucose tolerance tests and MGTT in nondiabetic (Gatti et al, 1984;Jarjis et al, 1984;Heijnen et al, 1995) and diabetic (Gatti et al, 1984;Fuessl et al, 1986;Ebeling et al, 1988) subjects, although Williams et al (1980) reported no effect. In people with diabetes, medium-to long-term (range 4 weeks to 1 y) guar gum supplementation (9-60 g/day) also has shown metabolic improvements in blood glucose control (Aro et al, 1981;Gatti et al, 1984;Kirsten et al, 1992;Groop et al, 1993). However, many studies have reported no effect on glycemic control (Cohen et al, 1980;Uusitupa et al, 1989;Wilson et al, 1989); the dose of guar gum or the method of guar gum preparation and timing of delivery may be the reason for the discrepancy between studies on glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Dubois et al (43) suggest that meals with < 18% of energy from fat do not evoke an increase in plasma triacylglycerol concentrations. Most postprandial studies in the literature used higher dietary fat intakes, usually 40-50% of energy, to evoke alimentary lipemia (4,8,9,27,44); however, even low-fat diets will cause alimentary lipemia. The increase in plasma and TRL-triacylglycerols is due to an accumulation of both chylomicron remnants and hepatic VLDLs (27).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber alters postprandial glycemia and insulinemia in both healthy (9,16) and diabetic subjects (9,17,18). Many of the studies reporting such effects of fiber have tested isolated fiber sources independent of consumption of a complete mixed meal.…”
Section: Introductionmentioning
confidence: 99%